Asthma Increases Susceptibility to Heterologous but Not Homologous Secondary Influenza - Furuya, Yoichi (American Society for Microbiology, 2014)
Asthma was the most common comorbidity observed among patients hospitalized with influenza A virus during the 2009 pandemic. However, little remains known about how the asthmatic phenotype influences protective immune responses against respiratory viral pathogens. Using the ovalbumin-induced allergic lung inflammation model, we found that asthmatic mice, unlike nonasthmatic mice, were highly susceptible to secondary heterologous virus challenge. While primary virus infection generated protective memory immune responses against homologous secondary virus challenge in both asthmatic and nonasthmatic mice, full protection against heterologous A/California/04/2009 (CA04) viral infection was observed only in nonasthmatic mice. Significant reductions in CA04-specific IgA, IgG, and IgM levels and in CA04-neutralizing activity of bronchoalveolar lavage fluid (BALF) was observed following secondary CA04 challenge of PR8-immunized asthmatic mice. Furthermore, transfer of immune BALF obtained from nonasthmatic, but not asthmatic, donors following secondary viral infection generated protection against CA04 in naive recipients. Nonspecific B-cell activation by CpG inoculation restored protection in PR8-immunized, CA04-challenged asthmatic mice. These results demonstrate a causal link between defective mucosal antibody responses and the heightened susceptibility of asthmatic mice to influenza infection and provide a mechanistic explanation for the observation that asthma was a major risk factor during the 2009 influenza pandemic. IMPORTANCE The prevalence of asthma worldwide is increasing each year. Unfortunately, there is no cure for asthma. Asthmatic individuals not only suffer from consistent wheezing and coughing but are also believed to be more prone to serious lung infections that result in bronchitis and pneumonia. However, little is known about the influence of asthma on host mucosal immunity. Here we show that antibody responses during secondary heterologous influenza infections are suboptimal and that this is responsible for the increased mortality in asthmatic mice from viral infections. Understanding the mechanism of increased susceptibility will aid in developing new antiviral therapies for asthmatic patients.